2010
DOI: 10.1007/s11858-010-0250-0
|View full text |Cite
|
Sign up to set email alerts
|

A brief history of mathematics education in Turkey: K-12 mathematics curricula

Abstract: In this study, we survey the history of mathematics education in Turkey starting with its historical roots in the foundation of the republic. The changes in mathematics education in Turkey over the last century are investigated through an analysis of changes in curricular documents for K-12 schools. We consider the factors and reasons affecting curriculum developments, changes in philosophy and structure in terms of standards, objective and instructions. This article utilizes archival research techniques by ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…When these five points are considered together, it can be observed that there have been minor changes in the presentation of the concept of irrational numbers in mathematics education programs throughout the history of the Republic of Türkiye, with significant changes starting around 1990 and especially in 2005. The reason for this may be attributed to the "National Education Development Project," which is considered a turning point in the history of the Turkish education system and was supported by the World Bank in the early 1990s, leading to curriculum development efforts in collaboration between the Ministry of National Education and academics (Argün et al, 2010). Additionally, the adoption of behaviorist learning theory before 2005 and constructivist learning theory after 2005 has influenced the presentation of concepts due to the differing perspectives of these two theories on knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…When these five points are considered together, it can be observed that there have been minor changes in the presentation of the concept of irrational numbers in mathematics education programs throughout the history of the Republic of Türkiye, with significant changes starting around 1990 and especially in 2005. The reason for this may be attributed to the "National Education Development Project," which is considered a turning point in the history of the Turkish education system and was supported by the World Bank in the early 1990s, leading to curriculum development efforts in collaboration between the Ministry of National Education and academics (Argün et al, 2010). Additionally, the adoption of behaviorist learning theory before 2005 and constructivist learning theory after 2005 has influenced the presentation of concepts due to the differing perspectives of these two theories on knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…[MoNE], 2004;2013). Although Turkey was one of the first countries to incorporate statistics and probability into elementary mathematics curricula, the concepts of likely and unlikely events are now introduced in eighth grade, in contrast to countries such as Australia or the United States (Argün et al, 2010;Batanero et al, 2018;Makar, 2018).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…A few studies examining the development of concepts in secondary school mathematics curricula in Turkey have carried out. Curriculum studies have mostly focused on a short history of mathematics education or on a general comparison of curricula in the context of change (Argün et al, 2010;Zeybek, 2012). On the other hand, some studies have addressed the comparison between countries (Güzel, Karataş & Çetinkaya, 2010) and teachers' opinions about the overall or a single component of the curriculum (Merter & Şan, 2012;Tuncel, 2015).…”
Section: Functions In Mathematics Curricula and Textbooksmentioning
confidence: 99%